2014
DOI: 10.1186/1471-2393-14-207
|View full text |Cite
|
Sign up to set email alerts
|

Understanding delayed access to antenatal care: a qualitative interview study

Abstract: BackgroundDelayed access to antenatal care ('late booking’) has been linked to increased maternal and fetal mortality and morbidity. The aim of this qualitative study was to understand why some women are late to access antenatal care.Methods27 women presenting after 19 completed weeks gestation for their first hospital booking appointment were interviewed, using a semi-structured format, in community and maternity hospital settings in South Yorkshire, United Kingdom. Interviews were transcribed verbatim and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
115
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 30 publications
15
115
0
2
Order By: Relevance
“…Therefore, in the Dodowa area, women who lived long distances from a health facility but experienced unwanted pregnancies could have been reluctant to walk to health facilities for ANC services. In addition, absence of a pregnancy ‘mindset,’ which is common in unexpected or unwanted pregnancy, could have exerted a negative influence on women’s use of ANC services [7,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the Dodowa area, women who lived long distances from a health facility but experienced unwanted pregnancies could have been reluctant to walk to health facilities for ANC services. In addition, absence of a pregnancy ‘mindset,’ which is common in unexpected or unwanted pregnancy, could have exerted a negative influence on women’s use of ANC services [7,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased maternal and neonatal risk levels were confirmed by different studies Wessel et al (2003); Haddrill et al (2014); Schultz and Bushati (2015). Neonaticide is also a rare but dramatic consequence of negation of pregnancy Craig (2004); Putkonen et al (2007); Huchzermeier and Heinzen (2015); Oberman (2003); Porter and Gavin (2010); Ellonen et al (2015).…”
Section: Introductionmentioning
confidence: 84%
“…In their study of the transition to first-time motherhood, Darvill et al identified changes in the woman's self concept as the major psychological issue associated to the maternal transition with three main themes: control, support and forming a family Haddrill et al (2014). The feeling of loss of control is related to different aspects; mostly frequent unpleasant physiological disorders in early pregnancy, rapid changes in body shape, reduced occupational freedom due to restricted mobility and additional mothering tasks and dependency on others.…”
Section: Psychological Issues In a Woman Who Becomes A Mothermentioning
confidence: 99%
See 2 more Smart Citations